International Trade / Theory and Evidence - Kaempfer William H; Markusen James R; Maskus Keith E; Melvin James R (Mcgraw Hill, Inc, 1995)
Preface, Technical Concepts and the Gains from Trade, Introduction, Supply and Production Possibilities, Preferences and Demand and Welfare, General Equilibrium in Open and Closed Economies, The Gains from Trade, Cause and Consequences of Trade, The Causes of International Trade, Differences in Technology, The Heckscher-Ohlin Model, The Specific-Factors Model, Government Policies as Determinants of Trade, Imperfect Competition as a Determinant of Trade and the Gains from Trade, Empirical Studies of Comparative Advantage Models, Trade Policy, Tariffs, Quotas and Other Nontariff Barriers, Preferential Trade Areas, The Political Economy of Trade Policy, Administered Protection, Factor Trade and Growth and the Theory of Direct Foreign Investment, Trade in Factors of Production, Direct Foreign Investment and Multinational Firms, Factor Accumulation and Intertemporal Trade, Index.